Ayurvedic Cooking Self-healing D2.5 - Usha Lad; Vasant Lad (Motilal Banarsidass Publishe, 2010)
Ayurveda, the ancient healing art of India, teaches that food plays an essential part in one's health and sense of well-being. Here is an authentic guide of the Ayurvedic approach to food and tasty vegetarian cooking. The recipes are formulated using herbs and spices to help balance constitution of each person. The effects of the foods on individual constitution are included with every recipe together with the medicinal properties of many of the foods. This is a cookbook and much more. The Chapters included in this book are on the principles of Ayurveda and individual constitution; maintaining one's health, digestion and constitutional balance; the importance of proper food combining for optimal well-being; setting up an Ayurvedic kitchen and planning menus inclusive of every member of your family; and more than 100 recipes of delicious Ayurvedic cuisine. Three more important sections are included-nearly three hundred simple remedies for everything from the common cold and skin problems to stabilizing blood sugar in diabeties, all using familiar household herbs, fruits and vegetables; a chart for determining your individual constitution; comprehensive food guide lines; and a listing of the qualities of foods and their effects on the doshas.
Text language (ISO-639-1 code): en